Clinical Audit of Electronic Health Records to Identify Prediabetic Patients and Compliance with ICGP Guidelines in their Management - Castledine, Robert; Matuschka, Victoria; O’Reilly, Eimear (International Journal of Medical Students, 2023)
BACKGROUND: Current Irish College of General Practitioners (ICGP) Guidelines recommend that all patients with prediabetes have repeat HbA1c testing within 12 months, in addition to BMI and blood pressure measurement. It is also recommended that patients are provided with lifestyle advice. We carried out a clinical audit of electronic health records at a Dublin GP practice to evaluate adherence with guidelines. METHODS: We searched electronic health records to identify all patients with HbA1c values between 42-48 mmol/mol dating back to 1 January 2016, excluding patients with a subsequent diagnosis of diabetes. We manually reviewed the records of 129 included patients to extract the relevant data. RESULTS: 40.3% of patients had correct diagnosis coding. 74.4% of patients had their blood pressure checked within 2 months of a HbA1c result, whereas only 48.1% had their weight recorded. Of 81 patients with an initial HbA1c over 12 months previously, 66.6% had repeat testing within this period, and 33.3% of patients were either tested later or had no follow-up testing. A reference to lifestyle advice was made in the records of 52.7% of patients. CONCLUSION: Management for a significant proportion of patients did not meet standards as per ICGP Guidelines. To improve this, we coded all patients with pre-diabetes and placed a reminder of their electronic chart to recheck Hba1c, BMI and BP within 12 months. We conducted an educational meeting with practice clinicians regarding ICGP guidelines. The plan is to re-audit at 6 and 12 months to evaluate the benefit of intervention.